Meta‐analysis and trial sequential analysis of triclosan‐coated sutures for the prevention of surgical‐site infection. Issue 2 (17th January 2017) - de Jonge, S. W.; Atema, J. J.; Solomkin, J. S.; Boermeester, M. A.
Abstract: Background: Triclosan‐coated sutures (TCS) were developed to reduce the risk of surgical‐site infection (SSI). Level 1A evidence of effectiveness has been presented in various recent meta‐analyses, yet well designed RCTs have not been able to reproduce these favourable results. The aim of this study was to evaluate all available evidence critically with comprehensive analysis to seek a more reliable answer regarding the effectiveness of TCS in the prevention of SSI. Methods: PubMed, MEDLINE, Embase and Cochrane Library databases were searched from 1990 to November 2015 for RCTs that compared TCS with sutures that were exactly the same, but uncoated, in the prevention of SSI. Pooled relative risks (RRs) with corresponding 95 per cent confidence intervals were estimated using a random‐effects model. Metaregression was used to substantiate subgroup effects, trial sequential analysis was employed to assess the risk of random error, and quality of evidence was determined using Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results: Twenty‐one RCTs including 6462 patients were included. Risk of bias was serious. Pooled effects showed a RR of 0·72 (95 per cent c.i. 0·60 to 0·86; P < 0·001) for all publications. At a risk of 138 SSIs per 1000 procedures, the use of TCS reduced this by 39 (95 per cent c.i. 19, 55). Trial sequential analysis confirmed a RR reduction of 15 per cent for the use of TCS. Conclusion: GRADE assessment shows moderate‐quality evidence that TCS are effective in reducing SSI. Trial sequential analysis indicates that the effect was robust, and additional data are unlikely to alter the summary effect. Abstract : The final word?